PENGARUH LOKASI, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Kafe Sabanhari Tangerang Selatan) - Handayani, Esti Tri (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to examine how much influence location, promotion and service quality have on purchasing decisions (Case study of the Sabanhari cafe, South Tangerang). The number of samples in this study that used a minimum of 160 respondents. The data collection method used is a survey, the research instrument is a questionnaire. The data analysis method used is descriptive analysis and the hypothesis is tested using the Structural Equation Model (SEM) with the Smart- PLS (Partial Least Square) program. The results of this study indicate that the location variable is positively significant on purchasing decisions, Promotion is positively significant on purchasing decisions, and Service Quality is positively significant on purchasing decisions.